The Role of Environmental Endocrine Disruptors on Leydig Cell Death and Senescence - Fang Yang; Xiaoya Li; Meijing Wang; Xiucheng Lan; Jingyi Zhang; Junjun Li; Degui Chang; Xujun Yu (The World Journal of Men's Health)
Environmental endocrine disruptors, as exogenous chemicals that interfere with hormonal behavior, are known to cause testicular Leydig cell death and senescence. The incidence of diseases of the male reproductive system has been increasing over the past half-century. Genetic defects alone cannot explain the rapid increase in incidence, and there is growing evidence that environmental factors or lifestyle changes are responsible for the high incidence in recent years. Testicular Leydig cells occupy an important role in the male reproductive system. In this study, we review the mechanisms by which environmental endocrine disruptors promote both death and senescence of testicular Leydig cells, refine the former into two programmed death modes, apoptosis, and autophagy, and further explore the interactions among them, thus summarizing the advances of the toxic effects of environmental endocrine disruptors on testicular Leydig cells, and expecting to provide a new therapeutic idea.